COMPLEMENT-DEPENDENT TRANSPORT OF ANTIGEN INTO B CELL FOLLICLES - Gonzalez, Santiago F. (2010)
Since the original proposal by Fearon that the Complement System linked innate and adaptive immunity (1), there has been a rapid expansion of studies on this topic. With the advance of intravital imaging, a number of recent papers have revealed an additional novel pathway in which complement C3 and its receptors enhance humoral immunity through delivery of antigen to the B cell compartment. In this review, we will discuss this pathway and highlight several novel exceptions recently found with a model influenza vaccine such as: (a) MBL opsonization of influenza and uptake by macrophages; (b) and capture of virus by dendritic cells residing in the medullary compartment of peripheral lymph nodes.